The Fc Orth(SA) final examination. How effective is the written component? - Swanepoel, Stefan (Division of Orthopaedic Surgery, 2020)
Background: To determine the pass rate of the ﬁnal exit examination of the College of Orthopaedic Surgeons of South Africa [FC Orth(SA)] and to assess the correlation between the written component with the clinical and oral component. Methods: Results of candidates who participated in the FC Orth(SA) ﬁnal examination during a 12-year period from March 2005 through to November 2016 were assessed retrospectively. Pass rates and component averages were analysed using descriptive and inferential statistics. Spearman's rho test was used to determine the correlation between the components. Results: A total of 399 candidates made 541 attempts at the written component of the examination; 71.5% of attempts were successful and 387 candidates were invited to the clinical and oral component, of which 341 (88%) candidates were certiﬁed. The second-attempt pass rate for those candidates who wrote the written component again was 42%. The average annual increase in the number of certiﬁed candidates was 8.5%. The overall certifying rate increased by 1.5% for this period. Invited candidates who scored less than 54% for the written component were at significant risk of failing the clinical and oral component. The written component showed weak correlation with the clinical and oral component (r=O.48). Conclusion: While the written component was found to be an effective gatekeeper, as evidenced by a high eventual certifying rate, the results of this component of the FCOrth(SA) ﬁnal examination did not correlate strongly with the performance in the clinical and oral component. This ﬁnding conﬁrms the value of the written component as part of a comprehensive assessment for the quality of orthopaedic surgeons.